2008
DOI: 10.2319/121306-511.1
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Versus Nonpolarized Digital Images for the Measurement of Demineralization Surrounding Orthodontic Brackets

Abstract: A cross-polarization filter enhances the subjective assessment of demineralized lesions surrounding an orthodontic bracket and improves the reproducibility of measuring the lesion area. The filter did not improve the assessment of changes in enamel gray levels with demineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Additionally, a cross-polarizing technique was applied [15]. The image quality of the camera was set to 'fine' and the ISO sensitivity was set to 200.…”
Section: Sample and Photographic Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a cross-polarizing technique was applied [15]. The image quality of the camera was set to 'fine' and the ISO sensitivity was set to 200.…”
Section: Sample and Photographic Techniquementioning
confidence: 99%
“…Further, measurements of WSLs using different image processing techniques and digitally converted photographs were suggested and various researchers have confirmed the reproducibility and reliability of these methods [11][12][13][14]. Comparing polarized vs nonpolarized photographs showed that the use of a crosspolarizing filter decreases the accompanying flash reflection on digital images, thereby improving the subjective assessment of demineralized lesions surrounding an orthodontic bracket and enhancing the reproducibility of demineralization area measurements [15].…”
Section: Introductionmentioning
confidence: 97%
“…One of the strengths of our study is the methods of evaluation that were utilized, as we Our objective measure of improvement assessed the change in percent of tooth surface affected (proportional change), which has been used in many previous studies 15,[17][18][19][20] , rather than absolute measurements of luminance or size 21,22 . The comparison of proportional change also allows for us to account for any differences in magnification and angulations of teeth, when using photograph images.…”
Section: Wsl Surface Areamentioning
confidence: 99%
“…Using the Kubelka-Munk equations, Ko et al [36] showed that the optical scattering power correlated with mineral loss and yielded improved results over reflectance measurements. Benson et al [44] demonstrated that the visibility of scattering structures on highly reflective surfaces such as teeth can be enhanced by the use of crossed polarizers to remove the glare from the surface due to the strong specular reflection from the enamel surface [44,45]. The contrast between sound and demineralized enamel can be further enhanced by depolarization of the scattered light in the area of demineralized enamel [46,47].…”
Section: Reflectance Spectroscopymentioning
confidence: 99%